1996
DOI: 10.1016/0014-5793(96)00804-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic glutamate treatment of cultured cerebellar granule cells induces Ca2+‐dependent collapse of mitochondrial membrane potential and ultrastructural alterations of mitochondria

Abstract: Rhodamine 123 staining and electron microscopy were used to reveal a correlation between the ultrastructural and functional state of cultured cerebellar granule cells after short glutamate treatment. Glutamate exposure (15 min, 100 lxM) in Mg2+-free solution caused considerable ultrastructural alterations in a granule cell: clumping of the chromatin, swelling of the endoplasmic reticulum and mitochondria, and disruption of the mitochondrial cristae. After glutamate treatment, the mitochondria of the neurons lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 19 publications
4
57
0
Order By: Relevance
“…By using the¯uorescent probe JC-1, glutamate was suggested to mediate signi®cative changes in the mitochondrial membrane potential (Ankarcrona et al, 1995;Stout et al, 1998). Isaev et al (1996) have also observed that glutamate collapsed the mitochondrial membrane potential, since the neuronal cells lost the ability to accumulate rhodamine 123, a membrane potential-dependent probe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using the¯uorescent probe JC-1, glutamate was suggested to mediate signi®cative changes in the mitochondrial membrane potential (Ankarcrona et al, 1995;Stout et al, 1998). Isaev et al (1996) have also observed that glutamate collapsed the mitochondrial membrane potential, since the neuronal cells lost the ability to accumulate rhodamine 123, a membrane potential-dependent probe.…”
Section: Discussionmentioning
confidence: 99%
“…Under this perspective, mitochondria has been considered to be a target for glutamate neurotoxicity, because it plays an important role in bu ering intracellular Ca 2+ after glutamate exposure (Budd and Nicholls, 1996;Wang and Thayer, 1996). Moreover, a Ca 2+ -dependent disturbance of mitochondrial membrane potential, associated with ultrastructural alterations, was demonstrated to depend upon the activation of NMDA receptors (Isaev et al, 1996). Additionally, the entry of Ca 2+ through the NMDA and the non-NMDA receptors has been shown to mediate the formation of ROS (Lafon-Cazal et al, 1993;Bindokas et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, factors that modulate mitochondrial Na¤-Ca¥ exchange activity would have a substantial influence on the recovery of these responses. A number of recent studies have documented the Ca¥-dependent effects of NMDA receptor activation on Øm (Ankarcrona et al 1995;Isaev, Zorov, Stelmashook, Uzbekov, Kozhemyakin & Victorov, 1996;White & Reynolds, 1996;Schinder et al 1996;Nieminen, Petrie, Lemasters & Selman, 1996) in several neurone types. Depolarization of Øm could result either from Ca¥ cycling through mitochondria resulting in net positive charge entry into the matrix (Nicholls & Akerman, 1982), or from opening of the PTP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by this laboratory and others have shown that NMDA-receptor activation results in a loss of mitochondrial membrane potential (z~I'),which is Ca2~dependent (Budd and Nicholls, 1996;Isaev et al, 1996;Nieminen et al, 1996;Schinder et al, 1996;White and Reynolds, 1996) and can be prevented by Glutamate is an endogenous neurotoxin that causes injury at least partially as a result of large increases in intracellular calcium concentration (Ca2+~Mito-chondria have been shown to buffer changes in l~Ca2~]ã fter glutamate-receptor activation in cultured central neurons (Kiedrowski and Costa, 1995;White and Reynolds, 1995). However, several studies have shown that excessive increases in~Ca2~] 1can result in mitochondrial calcium overload and subsequent production of reactive oxygen species (ROS) (Flamm et a!., 1978;Chance et al, 1979;Halliwell, 1989;Beal, 1992).…”
mentioning
confidence: 93%